Learning Efficiency of Student of PG-PAUD FKIP Study Program of Universitas Riau - N., Zulkifli; Solfiah, Yenny (Proceedings of the 1st UR International Conference on Educational Sciences, 2017)
The learning efficiency of teachers candidate, especially those of Early Childhood Education (ECE) need to pay serious attention because of their strategic role in preparing golden generation for the next 45 years of Indonesian people qualified and competitive. The purpose of the study was to describe the category of the students learning efforts and achievement of PG PAUD Study Program of FKIP Universitas Riau. The methodology used is âsurveyâ in the form of quantitative descriptive research. The research found out that the students learning efficiency by and large falls in three categories;high (39%), moderate (35%), and low (26%), and the cumulative achievement index of the students is also in three categories, very good (31%), good (97%) and Middle(0,78%). But, in general, the students learning efficiency scores falls in the high category (79,97%), and the cumulative achievement index of the students is also in good and very good category.